2007
DOI: 10.1086/511799
|View full text |Cite
|
Sign up to set email alerts
|

Getting a Job: Is There a Motherhood Penalty?

Abstract: Survey research finds that mothers suffer a substantial wage penalty, although the causal mechanism producing it remains elusive. The authors employed a laboratory experiment to evaluate the hypothesis that status-based discrimination plays an important role and an audit study of actual employers to assess its real-world implications. In both studies, participants evaluated application materials for a pair of same-gender equally qualified job candidates who differed on parental status. The laboratory experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
799
5
32

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,732 publications
(868 citation statements)
references
References 46 publications
32
799
5
32
Order By: Relevance
“…These results are in line with findings from earlier studies that find profound evidence of a parenthood wage penalty in the United States (Correll et al, 2007;Budig and Hodges, 2010). Apparently, such penalties are not specific to the United States but also evident in the Netherlands.…”
Section: Testing For Human Capital Effectssupporting
confidence: 92%
See 2 more Smart Citations
“…These results are in line with findings from earlier studies that find profound evidence of a parenthood wage penalty in the United States (Correll et al, 2007;Budig and Hodges, 2010). Apparently, such penalties are not specific to the United States but also evident in the Netherlands.…”
Section: Testing For Human Capital Effectssupporting
confidence: 92%
“…Existing research confirms that employers' hiring decisions are strongly influenced by one's parenthood status (Budig and England, 2001;Budig and Hodges, 2010;Correll et al, 2007;England, 2005;Gangl and Ziefle, 2009). The literature suggests that employers discriminate against working mothers in terms of hiring decisions, promotion opportunities, and wages, but not against fathers.…”
Section: Variations Of Unemployment Stigma Across Age Parenthood Etmentioning
confidence: 88%
See 1 more Smart Citation
“…Additionally, the field experiment measures people's real behavior in their social lives, which has more external validity than in laboratory experiment settings. In past sociological studies, the field experiment method has mainly been used to study discrimination (e.g., Correll et al, 2007;Pager et al, 2009;Tilcsik, 2011). We recommend that researchers may adapt the field experiment method to studying broader topics concerning different types of interpersonal relationships, such as friendship, dating, risk sharing, assistance, and so on.…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18] For example, an elegant study conducted by Correll et al identified a "motherhood penalty," where indicating membership in the elementary school parent-teacher organization on one's curriculum vitae hurt women's chances of employment and pay, but actually helped men. 19 Gender stereotypes exist, even among those who do not support their content. The universal reinforcement of such stereotypes over time leads to implicit but prescriptive rules about how women and men should act.…”
mentioning
confidence: 99%